Chemical shift MR imaging in the lumbar vertebra: the effect of field strength, scanner vendors and flip angles in repeatability of signal intensity index measurement. Issue 1 (December 2016) - Xiao, Zebin; Li, Jian; Li, Chengqi; Zhang, Yuyang; She, Dejun; Cao, Dairong
Abstract Background To evaluate the reproducibility of signal intensity index (SII) measurements with MRI systems from different vendors and with different field strengths, and to test the effectiveness of flip angle. Methods Thirty-two healthy volunteers (mean age 35.3 ± 9.3 years) were enrolled in this ethics committee-approved study. Chemical shift MR imaging was performed on 1.5- and 3.0-T MR systems from three vendors. Two independent observers measured SII values in five lumbar segments. Inter- and intraobserver agreement was assessed using the interclass correlation coefficients (ICCs). Differences of mean SII values between different field strengths and MR vendors as well as flip angles were compared by using repeated-measures analysis of variance. Differences of mean SII values between different flip angles were also compared by using paired-samplet test. Results Inter- and intra-observer correlation coefficients showed good agreement (all ICC > 0.75) when measuring SII values at different MR systems (ICCs ranging from 0.896 to 0.983) and flip angles (ICCs ranging from 0.824 to 0.983). There were no significant differences in mean SII values measured by different MR vendors with different field strengths (allp > 0.05 ranging from 0.337 to 0.824). The differences in the mean SII between the four different flip angles were statistically significant (allp < 0.05 ranging from < 0.001 to 0.004) except the group of flip angle 50° versus 70° (p = 0.116). Conclusion The SII measurement using chemical shift MR imaging may be comparable between different MR systems. Also high flip angles showed better stability to quantitate lumbar fat content.